AGRIDEAL Magazine: The River Between Botswana, Mozambique, South Africa, Zimbabwe - Takavarasha, Tobias (Agri Connect (Pty) Ltd, 2013)
Ten years ago an experiment began in the Limpopo River Basin. Hundreds of farmers, dozens of researchers and a handful of development partners embarked on a journey that continues today. That journey is the Challenge Program on Water and Food, the CPWF.